Formation of Civil Society Through CSR in Jababeka Industrial Estate Cikarang - Ida Abdul Gopar (Kusuma Negara Business School, 2021)
Civil society is often positioned as an ideal way of life. From a historical perspective, Islamic thinkers usually refer to civil society under the leadership of the Prophet Muhammad. To realize a civil society in business, a transparent discussion is needed between all parties. Islam requires every business actor to always act impartially and protect the fulfillment of the rights of others, the rights of the social environment, and the rights of the universe. Therefore, social balance and a natural balance must be maintained together with business people. Corporate social responsibility is currently an absolute responsibility that must be carried out by companies in terms of maintaining and establishing social communication with the community and the surrounding environment. The purpose of this study was to determine the formation of civil society through Corporate Social Responsibility (CSR) in the Jababeka Cikarang Industrial Estate. This type of research is qualitative and descriptive field research. Researchers used data collection techniques through interviews. The results showed that the formation of civil society helped ease the economy of the community and the surrounding environment. However, the implementation of the CSR plan for the Jababeka industry has not been maximized. This is due to very limited participation and distribution is still consumptive, so community empowerment is not optimal. In addition, it can be concluded that the implementation of corporate social responsibility is by following per under Islamic business ethics.